Accounting System in Schools of Parsa - Dwibedi, Lalan (Academic Voices: A Multidisciplinary Journal, 2015)
Accounting system are often the most important formal sources of information in organizations. They are designed to provide all the levels of management with timely and reasonably accurate information to help them make decisions which are in agreement with their organization’s goal. This paper focuses on accounting practices used by schools of Parsa district. Basically, questionnaire and observation methods were used for the collection of relevant data. The findings reveal that majority of the schools of Parsa district do not keep proper records of the financial transactions. The schools need the use of modern equipment such as computers with trained human resources in preparing and storing financial records of their transactions to get up-to-date information whenever needed. DOI: http://dx.doi.org/10.3126/av.v4i0.12353 Academic Voices Vol.4 2014: 24-28